Estimates of traceability and certification of beef in Brazil (Research, Society and Development, 2022)
Bovine traceability is characterized by the control of all animals, taking care of the identification of each one from the moment of birth until slaughter. It also makes all necessary records during the life of the animal. It is important not only for monitoring the animal, but also for the consumer to know exactly the origin of the purchased product. The objective of the study was to evaluate the importance of traceability and certification of beef in Brazil. This is a literature review based on the collection of information available in Portuguese, English and Spanish, with a search in Lilacs, Medline, Scielo, PubMed, and Google Scholar databases. The period chosen for the study was between 2017 and 2021, using the keywords: Bovine traceability; bovine certification; beef; SISBOV. The results showed the need for greater knowledge and credibility on the implementation of the Brazilian System of Individual Identification of Cattle and Buffalo (SISBOV). It was concluded that ranchers are resistant to maintain a system of traceability and certification in their properties, since the cost with the implementation, as well as the labor generate many expenses to the properties. Some studies have also shown that the lack of obligation is a decisive factor for the non-acceptance of traceability systems.